Penerapan Konsep Wilayatul Hukmi Terhadap Shalat Gerhana Perspektif Fiqh Dan Astronomi - Darlius, Darlius (Sekolah Tinggi Agama Islam Negeri Majene, 2024)
The research related to the concept of wilyatul hukmi in determining the beginning of the qamariyah month which is used for the eclipse phenomenon, namely the implementation of eclipse prayer commands from the perspective of fiqh and astronomy. The purpose of this research is to disclose the implementation of wilayatul hukmi into eclipse prayers under the fiqh and astronomy perspectives. Both of them tried to find out the use of this concept in eclipse prayers. The research method used was qualitative with descriptive analysis data processing techniques. Where according to fiqh scholars, eclipse prayers are performed based on the meaning of the hadith text which states that if you see an eclipse, immediately pray and do not use calculations or news and are not tied to an area to perform the prayer. Meanwhile, according to astronomy, eclipse prayers are performed if the area is passed by an eclipse event and an area that is not passed by an eclipse event has no obligation to follow the legal policies of another area.